The chatter of the visible : montage and narrative in Weimar Germany - McBride, Patrizia C. (Knowledge Unlatched., 2016)
"Examines the paradoxical narrative features of the photomontage aesthetics of artists associated with Dada, Constructivism, and the New Objectivity. While montage strategies have commonly been associated with the purposeful interruption of and challenge to narrative consistency and continuity, McBride offers a historicized reappraisal of 1920s and 1930s German photomontage work to show that its peculiar mimicry was less a rejection of narrative and more an extension or permutation of it."